Gender Differences in Children’s Non-Leisure Activities: A Decomposition Analysis - Dayang Haszelinna Abang Ali; Rosita Hamdan; Audrey Liwan; Josephine Yau Tan Hwang (Economics and Finance in Indonesia, 2020)
The prevalence of son preference indicates that girls will have less leisure time compared to boys. This study aims to examine gender differences in weekly hours in schooling, housework, and working among children in Indonesia using Tobit Model and decomposition model of Bauer & Sinning (2005), to test whether son preference explains the differences. The dataset was drawn from the fourth wave of Indonesia Family Life Survey (IFLS) in 2007. The results show significant gender differences in housework and working for children aged 5–14 years and insignificant gender gap in schooling for both age groups. These results confirm the existence of gender differences among younger children compared to older children in their time allocation.